ber, ke, me, STRATEGI PROMOSI DAN INOVASI DALAM UPAYA PENINGKATAN DAYA SAING PENJUAL ES TEH INDONESIA DI KOTA BANGKALAN - iim, iim; Romiftahul Ulum (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This research aims to explore and analyze the promotional strategies and innovations implemented by Indonesian iced tea sellers in Bangkalan City, with a focus on efforts to enhance their competitiveness in an increasingly competitive market. This study employs a qualitative method involving in-depth interviews with business owners, employees, and customers to gain a comprehensive perspective on best practices and challenges faced. The research results from the promotion strategy and innovation of Indonesian iced tea sellers in Bangkalan City show that this brand has successfully transformed the image of iced tea into a high-value product with strategically located outlets. Sellers utilize social media, discounts, and partnerships with online ordering applications to attract customers. Product innovations, including flavor variations and attractive packaging, significantly contribute to increased revenue and customer loyalty. Despite facing challenges such as fierce competition and price fluctuations, the findings indicate that this adaptive and competitive approach is effective in maintaining competitiveness in the contemporary beverage market.